Mechanism for enhancement of electrical activation of silicon in GaAs by aluminum co-implantation - Souza, Joel Pereira de (2018)
A pronounced enhancement in the electrical activation of implanted Si in GaAs is demonstrated by co-implantation of Al. The maximum enhancement ( x 2) occurs when the Si distribution is shallow, there is a separation between the Si and Al distributions with the Al being deeper, the Si and Al are implanted at doses of 91 X 1013 cme2, and subsequent annealing of the co-implanted GaAs is performed under capless or proximity cap conditions. A model considering gettering of the oxygen present in the bulk Czochralski-grown GaAs to the implanted Al is invoked to explain the observed activation enhancement.